2019
DOI: 10.1101/790915
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Population genetic analysis of 12 X-STRs in a Bahraini population sample (Allele and haplotype frequencies of 12 X-STRs in Bahraini population)

Abstract: To date, there are very limited genetic studies conducted on the Kingdom of Bahrain and this is one of the first studies conducted to evaluate the 12 X-STRs included in the Investigator X-12 QS kit. Bahrain is a small archipelago located in the Arabian Gulf. X-STRs are very informative in population genetics studies, human identification and complex kinship analysis. One hundred and fifty-six (156) buccal swabs were collected using cotton from non-relatives' Bahraini males from four different regions of Bahrai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 21 publications
1
2
0
Order By: Relevance
“…This study confirms the findings of a previous mtDNA study of the Sorani Kurds, which found that they are genetically related to the European lineage [65]. Furthermore, based on X-STRs, the Bahraini and Emirati populations were more closely linked, supporting the findings of Al-Snan's previous study [30].…”
Section: Plos Onesupporting
confidence: 91%
See 2 more Smart Citations
“…This study confirms the findings of a previous mtDNA study of the Sorani Kurds, which found that they are genetically related to the European lineage [65]. Furthermore, based on X-STRs, the Bahraini and Emirati populations were more closely linked, supporting the findings of Al-Snan's previous study [30].…”
Section: Plos Onesupporting
confidence: 91%
“…This study looked into the structure of five geographical regions: 11 Middle Eastern countries and populations [30][31][32][33][34][35], three African regions [36][37][38], seven South Asian countries and populations [39][40][41][42][43][44], 17 European regions and populations [32,34,[45][46][47][48][49][50][51][52] and eight South American regions and populations [53,54]. STRUCTURE output was processed with STRUC-TURE HARVESTER to analyse and display likelihood values across numerous values of K, as well as to determine the number of genetic groupings that best suit the data [55,56].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation